In vitro study of size-dependent inhibition of human cytochrome P450 (P450) P450-1A2, P450-2A6, P450-2B6, P450-2C8, P450-2E1, P450-2J2, and P450-3A5 by zinc oxide nanoparticles (ZnONPs) - Lamia Chowdhury; Yuh Fen Pung; Swee Yong Pung; Chin Eng Ong; Cin Kong; Yan Pan (Precision Nanomedicine)
Zinc oxide nanoparticles (ZnONPs) are employed widely in various fields. However, these ZnONPs may potentially inhibit enzyme activities. Cytochrome P450 (P450-) isozymes, which play a crucial function in human bio-transforming drugs, can be inhibited by ZnONPs, leading to slower clearance of co-administrated drugs and elevated drug plasma concentrations. This study aimed to reveal the inhibitory effects of the ZnO nano-sized particles, (<50 nm ZnONP50), (<100nm ZnONP100), and bulk particles (ZnOBP) on human recombinant P450-1A2, P450-2A6, P450-2B6, P450-2C8, P450-2E1, P450-2J2, and P450-3A5 under a size-dependent context. Fluorescence enzymatic assays were carried out to quantify enzyme activities in vitro. The results indicated that ZnO particles inhibited the tested P450 isozymes with varying potencies. ZnONP50 inhibited P450-2B6 and P450-2E1 with Ki values of 20.3 $μ$g/mL and 16.6$μ$g/mL following a mixed mode; inhibited P450-2C8 with Ki value of 43.3 $μ$g/mL competitively; inhibited P450-2J2 with Ki values of 8.2$μ$g/mL and 2. 5$μ$g/mL non-competitively. ZnONP100 inhibited P450-2B6 and P450-2E1 with Ki values of 6.7$μ$g/mL and 40.1$μ$g/mL following mixed mode; inhibited P450-2J2 with Ki value of 20.0$μ$g/mL following mixed or non-competitive mode; inhibited P450-3A5 with Ki value of 0.5$μ$g/mL non-competitively. ZnOBP competitively inhibited the enzymatic activity of P450-2E1 with Ki value of 28.3 $μ$g/mL. The inhibition potency observed for P450-2B6, P450-2J2, and P450-2E1 depended on the size of the ZnO particle. In conclusion, the interactions between ZnONP products and co-administered drugs metabolized by these inhibited P450-isozymes should be further investigated using in vivo models. Additionally, in silico studies are recommended to characterize these interactions at the molecular level.